2014
DOI: 10.1002/mdc3.12103
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Efficacy of Screening Algorithms for Assessing Deep Brain Stimulation Candidacy in Parkinson's Disease

Abstract: Background Deep Brain Stimulation (DBS) for Parkinson disease (PD) may be underutilized because of limited access to care (most DBS surgeries are performed at specialized centers) or over-referral of poor candidates, leading to inequitable utilization of limited evaluative resources. There is a pressing need for a widely employable screening algorithm to aid in the evaluation of PD candidates for DBS. Objective To compare the validity and efficacy of two published screening algorithms, the Florida Surgical Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…33 Another center reported that despite passing screening, about 9% of those on the DBS-evaluation pathway were excluded for dementia and about 4% for depression on the basis of neuropsychological evaluation. 35 These findings again highlight the importance of neuropsychological evaluation. It appears rare that persons identified as having normal or only very mildly impaired cognition by full neuropsychological evaluation go on to develop disabling cognitive deficits soon after DBS, although such cases have been reported.…”
Section: Reasons For Screening/evaluation Failuresmentioning
confidence: 89%
See 3 more Smart Citations
“…33 Another center reported that despite passing screening, about 9% of those on the DBS-evaluation pathway were excluded for dementia and about 4% for depression on the basis of neuropsychological evaluation. 35 These findings again highlight the importance of neuropsychological evaluation. It appears rare that persons identified as having normal or only very mildly impaired cognition by full neuropsychological evaluation go on to develop disabling cognitive deficits soon after DBS, although such cases have been reported.…”
Section: Reasons For Screening/evaluation Failuresmentioning
confidence: 89%
“…Both the referral of persons for whom DBS is inappropriate and nonreferral of those for whom DBS is appropriate diminish the efficiency of the presurgical patient-selection process. 23,28 At least two standardized questionnaires have been developed for use by referring primary-care physicians and non-subspecialists in movement disorders to enhance referral of those persons for whom DBS has a high likelihood of being an appropriate treatment. The Florida Surgical Questionnaire for Parkinson Disease (FLASQ-PD) was developed at one US movement-disorder surgery center (University of Florida) to improve surgical referral patterns.…”
Section: Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…An observational study in Germany and Spain showed that the selection rate for DBS was significantly higher for patients in which the Stimulus tool had been used compared to the unscreened population (77 versus 48 %, respectively) [ 8 ]. A recent single-centre study in the USA showed that Stimulus was superior to another tool in predicting DBS candidacy in patients with PD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%